2019
DOI: 10.1071/an18210
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of glycerol in pigs fed diets containing mixed crude glycerin and β-adrenergic agonist

Abstract: The optimised use of mixed crude glycerin (MCG) and ractopamine hydrochloride (RH) in diets for finishing pigs requires a better understanding of glycerol metabolism. Therefore, the present study evaluated the performance, blood parameters, metabolite concentrations in the Longissimus lumborum muscle and the activity of enzymes in the liver, subcutaneous adipose tissue and kidney of pigs fed diets containing MCG and/or RH. According to the initial weight, 64 barrows were distributed in a 4 × 2 factorial design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 156 publications
0
2
0
Order By: Relevance
“…Present study data is consistent with Mousa et al (2018) who observed that crude glycerol supplementation in the broilers did not show any significant effect on serum total protein, albumin, globulin, serum glucose and HDL level. Pinto et al (2019) who reported that blood glucose, total protein, albumin did not differ significantly among the treatment groups in the pigs fed diet containing mixed crude glycerine and ractopamine hydrochloride. Serum protein and uric acid concentration remain quiet similar between the groups (Erol et al 2009) The litter moisture (%) of various treatment groups fed with glycerol with or without probiotic is shown Table 4.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Present study data is consistent with Mousa et al (2018) who observed that crude glycerol supplementation in the broilers did not show any significant effect on serum total protein, albumin, globulin, serum glucose and HDL level. Pinto et al (2019) who reported that blood glucose, total protein, albumin did not differ significantly among the treatment groups in the pigs fed diet containing mixed crude glycerine and ractopamine hydrochloride. Serum protein and uric acid concentration remain quiet similar between the groups (Erol et al 2009) The litter moisture (%) of various treatment groups fed with glycerol with or without probiotic is shown Table 4.…”
Section: Resultsmentioning
confidence: 98%
“…Haematological and blood biochemical profile of experimental broiler chickens fed glycerol with or without probiotic by glycerol supplementation Pinto et al (2019). reported that serum cholesterol level did not affected by supplementation of glycerol.Mousa et al (2018) reported that LDL level was significantly reduced in birds fed diet with 5% crude glycerol compared to broilers fed standard diet which recorded highest value.…”
mentioning
confidence: 99%